INSTITUSIONALISASI PARTAI POLITIK OLEH DEWAN PENGURUS WILAYAH PARTAI PERSATUAN INDONESIA (DPW PARTAI PERINDO) PROVINSI RIAU - Fajar Rizqy Matra Marta; Adlin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
As a newly established political party, this is a significant step for PERINDO's party, especially in Riau province, so that the writer is interested to examine how this new political party is establishing its institutionalization at the level of Riau Province Board. In addition, the authors also want to examine what factors become obstacles faced by Dewan Pimpinan Wilayah (DPW) PERINDO Riau Province Party in conducting institutionalization. The research problem can be formulated as follows: How is the institutionalization of political party by the Dewan Pimpinan Wilayah of the Persatuan Indonesia Party (DPW PERINDO Party) Riau Province ?. What factors are the obstacles experienced by the Dewan Pimpinan Wilayah of the Persatuan Indonesia Party (DPW PERINDO Party) Riau Province in conducting the institutionalization of the political party ?. The purpose of this research is: To know the institutionalization political party conducted by the Dewan Pimpinan Wilayah of the Persatuan Indonesia Party (DPW PERINDO Party) Riau Province. To know what factors become obstacles experienced by the Dewan Pimpinan Wilayah of the Persatuan Indonesia Party (DPW PERINDO Party) Riau Province in conducting institutionalization of the political party. Qualitative research methods. Location of research in DPW PERINDO Riau Province Party. Primary data sources through interviews as well as secondary data sources. Data analysis technique is conducted by qualitative descriptive analysis. The Dewan Pimpinan Wilayah of the Persatuan Indonesia Party (DPW PERINDO Party) Riau Province as part of the PERINDO party in the activity of carrying out the functions of political parties is not allowed to leave and always guided by the Statutes / Bylaws and other rules applicable in the party PERINDO. The identity of the values put forward by is the strengthening of the Indonesian nation in the field of economic populist. DPW PERINDO Party of Riau Province has not implemented any connection binding with any party in decision making. While regarding the financing of the Dewan Pimpinan Wilayah of the Persatuan Indonesia Party (DPW PERINDO Party) Riau Province is still self-supporting. DPW PERINDO Riau Province Party in making the knowledge or positive image in the middle of society still depends on what is done by DPP PERINDO party. Factors inhibiting the Institutionalization of Political Parties DPW PERINDO Party Riau Province: funding, human resources, new political parties. Keywords: institutionalization, political party